Meninas confinadas. Perfil das jovens em cumprimento de medida de internação em São Paulo e no Pará - Souza, Luís Antônio Francisco de [UNESP] (2014)
The Brazilian Social-Education System is growing in terms of the young people doing time. This situation is more pervasive in relation to the girls, particularly in São Paulo state, where the recent figures show a massive expansion in the incarceration of young female. Because of that, the present article tries to compare the juvenile incarceration systems of São Paulo and Para states. This comparative strategy allows us to make sense of the reasons behind the growth of the young female incarceration rates in terms of the change of profile, the growth of criminal acts or the police-justice selectiveness strategies that could increase the female victimization in the context of a broad drugs use in our society.